Improving the quality of colonoscopy: Impact of efficient and safer preparation protocols and shorter waiting times - Aygün, Cem (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Aygün C. Improving the quality of colonoscopy: Impact of efficient and safer preparation protocols and shorter waiting times. Turk J Gastroenterol 2018; 29: 4-6.